Optimizing Tissue Use: A Step-wise Approach to Diagnosing Squamous Cell Lung Carcinoma on Small Biopsies - Coral Olazagasti; Isabel Preeshagul; Mohamed Aziz; Nagashree Seetharamu (SAGE Publishing, 2020)
Background: Histologic subtyping of lung cancer has significant implications for treatment planning. Accurate diagnosis based on cytology/small biopsy specimens is challenging and frequently determined by morphology, as material is often not sufficient for immunohistochemical studies (IHC). We investigated the concordance between the rates of diagnosis from cytology/small biopsies compared with surgical specimens in patients with squamous cell lung cancer (SCC) and the utility of IHC for diagnostic precision in lung cancer subtyping. Methods: We conducted a 5-year retrospective analysis identifying cases of SCC diagnosed on cytology/small biopsies ± IHC and compared them with subsequent surgical specimens when available. The number of patients with SCC on surgical biopsy and the concordance between cytology ± IHC was determined. Results: Over the 5-year period (2011-2015), 231 cases were identified. Surgery was performed on 66 cases (28.5%), of which 87.9% concurred with cytological diagnosis (95% exact binomial confidence interval [CI] = 77.5%-94.6%). There were 36 cases diagnosed in 2014 and 2015 with IHC data. Of those cytology cases with IHC (n = 12), SCC was confirmed by surgery in 91.7% (95% CI = 61.5%-99.8%). Of those without IHC (n = 24), 95.8% were confirmed SCC by surgery (95% CI = 78.9%-99.9%). These rates were not different (Fisher exact test). All cases with IHC were morphologically squamous. Conclusions: Our data demonstrate that diagnostic precision of identifying SCC by cytology/small biopsy is comparable with or without additional IHC studies. We recommend judicious use of IHC on cytology specimens, reserving it for cases where cytomorphology is equivocal. Tissue should be preserved for molecular analysis, which may have therapeutic implications.